Sustainable Islamic Business Models: A Case Study of Green-Tech Startups in Central Java, Indonesia - Maiza Fikri; Marlien Marlien; Amira Ibrahim Karim mohamed (International Forum of Researchers and Lecturers, 2024)
This study investigates sustainable Islamic business models through a qualitative case study of green-tech startups in Central Java, Indonesia. Using semi-structured interviews with founders, managers, and employees, complemented by secondary data from business reports and sustainability disclosures, the research examines how Islamic ethical principles, including stewardship (khalifah), social welfare (maslahah), and justice (adl), are integrated into operational practices and sustainability strategies. The purposive selection of 3–5 startups enables an in-depth exploration of organizational decision-making, innovation adoption, and environmental and social performance. Thematic analysis identifies recurring patterns in ethical integration, technological innovation, and sustainability outcomes. Findings reveal that Islamic startups effectively embed ethical values into operations, fostering environmental accountability through renewable energy initiatives, waste reduction, and resource optimization, while enhancing community engagement and equitable service delivery. Technological innovations such as IoT, AI, and blockchain further support sustainability performance, enabling startups to monitor and optimize environmental outcomes without compromising financial viability. Comparative analysis demonstrates that Islamic startups outperform non-Islamic counterparts in key sustainability metrics, including carbon reduction and social impact, highlighting the competitive advantage of ethics-driven entrepreneurship. Overall, the study confirms that Islamic ethical frameworks foster both environmental accountability and technological innovation, providing a practical model for sustainable development in emerging economies. These findings offer valuable insights for policymakers, investors, and entrepreneurs seeking to align ethical, social, and environmental objectives with business strategy.